EXTRACTION OF CROSSOPTERYX FEBRIFUGA STEM BARK AND ACUTE TOXICITY STUDIES LD₅₀ ON ALBINO RATS - Efusiauten, O. N.; Ardo, M. B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The research was undertaken to determine extraction of Crossopteryx febrifuga stem bark and acute toxicity studies on albino rats. The stem bark of C. febrifuga plant collected from Sebore farm,Mayo belwa, Adamawa state was identified, shade-dried at room temperature, grinded into fine powder using pestle and mortar. Fifty-four (54) healthy albino rats were divided into three groups with 18 rats per group to determine the median lethal dose (LD50) of each extract (ethanol, ethyl acetate and aqueous). The result of LD50 calculated were 5336.67 mg/kg body weight, 5890.0 mg/kg body weight, and 5776.67 mg/kg body weight for ethanol, ethyl acetate, and aqueous extracts, respectively, indicating a wide margin of safety and are safe to use in animals. In conclusion, the extracts contain phytochemicals and hormones of veterinary importance and are safe to use in animals. Further studies on Pharmacological activities of the plant should be investigated in animals.